Advanced Adrenocortical Carcinoma: Current Perspectives on Medical Treatment - Araújo, Alexandra Novais; Bugalho, Maria João (Hormone and Metabolic Research, 2021)
Adrenocortical carcinoma (ACC) is a rare and aggressive malignancy. For stage I and II tumors, surgery is a curative option, but even in these cases recurrence is frequent. Practical guidelines advocate a combination of mitotane with etoposide, doxorubicin, and cisplatin as first-line therapy for metastatic adrenocortical carcinoma. However, this scheme presents limited efficacy and high toxicity. The use of Immune Checkpoint Inhibitors (ICI) and multi-Tyrosine Kinase Inhibitors (mTKI) has modified the approach of multiple malignancies. The expectation of their applicability on advanced adrenocortical carcinoma is high but the role of these new therapies persists unclear. This article provides a short summary of last years’ findings targeting outcomes, limitations, and adverse effects of these new therapeutic approaches. The results of recent trials and case series pointed pembrolizumab as the most promising drug among these new therapies. It is the most often used ICI and the one presenting the best results with less related adverse effects when in comparison to the standard treatment with mitotane. Hereafter, the identification of specific molecular biomarkers or immune profiles associated with ICI or mTKI good response will facilitate the selection of candidates for these therapies. So far, microsatellite instability and Lynch Syndrome related germline mutations are suggested as predictive biomarkers of good response. Contrarywise, cortisol secretion has been associated with more aggressive ACC tumors and potentially poor responses to immunotherapy.
Keywords: immune checkpoint inhibitors; multi-tyrosine kinase inhibitors; immunotherapy; mitotane